2010
DOI: 10.1021/ma101062j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymorphism and Crystallite Size on Dipole Reorientation in Poly(vinylidene fluoride) and Its Random Copolymers

Abstract: Poly(vinylidene fluoride) (PVDF) and poly(VDF-co-hexafluoropropylene) [P(VDF-HFP)] films having different polymorphisms and crystallite sizes but a similar crystal orientation (i.e., c-axes parallel to the film surface) were prepared by different film processing methods. Effects of polymorphism and crystallite size on the dipole reorientation behavior and electric energy storage/release were studied by electric displacement-electric field (D-E) loop measurements. Experimental results suggested that coupling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
157
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 42 publications
7
157
1
1
Order By: Relevance
“…Specially, P(VDF-HFP) exhibits high chemical resistance and high flexibility as a result of the presence of HFP. Additionally, it is more interesting that the introduction of HFP does not change the crystalline structure while mediating the degree [3,4] . In other words, the copolymer P(VDF-HFP) exhibits almost the same crystal structure as PVDF.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, P(VDF-HFP) exhibits high chemical resistance and high flexibility as a result of the presence of HFP. Additionally, it is more interesting that the introduction of HFP does not change the crystalline structure while mediating the degree [3,4] . In other words, the copolymer P(VDF-HFP) exhibits almost the same crystal structure as PVDF.…”
Section: Introductionmentioning
confidence: 99%
“…The successful grafting of PS side chains from the Cl sites in P(VDF-CTFE) 93/7 was con fi rmed by 19 F NMR, as shown in Figure 1 a. Peak assignment and corresponding integration are summarized in Table 1A and Table 1B , respectively.…”
Section: Synthesis and Molecular Characterization Of P(vdf-ctfe)-g -Pmentioning
confidence: 81%
“…Peak assignment and corresponding integration are summarized in Table 1A and Table 1B , respectively. Comparing the 19 F NMR spectra for P(VDF-CTFE) 93/7 and its PS-graft copolymers, the CTFE-related 19 F signals (peaks c, f, and k in Figure 1 a and Table 1A) disappeared in chemical Figure 1 . A) 19 F and B) 1 H NMR spectra of P(VDF-CTFE) 93/7 and P(VDF-CTFE)-g -PS graft copolymers with 17, 29, 34 and 45 wt-% PS.…”
Section: Synthesis and Molecular Characterization Of P(vdf-ctfe)-g -Pmentioning
confidence: 99%
“…It was found that both unstretched and stretched PVDF-CTFE were mostly in the nonpolar phase at zero electric field, Under electric field a transition to the polar phase was observed as evidenced by enhanced electric displacement under electric field. Furthermore, evidence for the presence of all three phases was presented by Guan et al [16] based on wide-angle x-ray diffraction and Fourier transform infrared spectroscopy experiments. Although the structural transformation pathway proposed by us has not yet been observed, the low transition barriers calculated above make it a strong candidate for explaining the fast chargedischarge cycles observed experimentally [2].…”
mentioning
confidence: 94%